Childhood and Parenting in Transnational Settings (International Perspectives on Migration,, 2018)
This book describes children and youth on the one hand and parents on the other within the newly configured worlds of transnational families. Focus is put on children born abroad, brought up abroad, studying abroad, in vulnerable situations, and/or subject of trafficking. The book also provides insight into the delicate relationships that arise with parents, such as migrant parents who are parenting from a distance, elderly parents supporting migrant adult children, fathers left behind by migration, and Eastern-European parents in Nordic countries. It also touches upon life strategies developed in response to migration situations, such as the transfer of care, transnational (virtual) communication, common visits (to and from), and the co-presence of family members in each other's (distant) lives. As such this book provides a wealth of information for researchers, policy makers and all those working in the field of migration and with migrants. The chapter 'Gendering Parenting Practices in Romanian Transnational Families' is open access under a CC BY 4.0 license via link.springer.com.